The effectiveness of quantum teaching learning model on improving the critical thinking skills and the social science concept understanding of the elementary school students - M. Ihsan Ramadhani; Yulia Ayriza (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2019)
The study aims at identifying the difference on the effectiveness between the Quantum Teaching Learning Model and the Expository Learning Model in improving the students’ critical thinking skills and concept understanding in Social Science. The method that has been selected is the quasi-experimental research using the non-equivalent pre-test and post-test control group design. Then, the subjects in the study are 22 students of Grade IV Gunung Raja State Elementary School as the experimental group and 23 students of Grade IV Pulau Sari 1 State Elementary School as the control group from the Academic Year 2015/2016. The selection of the experimental group and the control group is based on the students’ similar characteristics with random approach. Based on the results of the random sampling technique implementation, the students from Gunung Sari State Elementary High School is provided with the Quantum Teaching Learning Model (experimental group) while the students from Pulau Sari 1 State Elementary High School is provided with the expository learning model (control group). In analyzing the data that have been gathered, the researcher has conducted the independent sample t-test and the paired sample t-test with SPSS 23 for Windows. The results of the study show that the Quantum Teaching Learning Model has bee more effective in comparison to the Expository Learning Model for improving the students’ critical thinking skills with significance value 0.000 0.050. In the same time, the results of the study also show that the Quantum Teaching Learning Model has been more effective in comparison to the Expository Learning Model for improving the students’ Social Science concept understanding with significance value 0.000 0.050.